OBSERVATIONS ON ANTLER SHEDDING BY FEMALE BARREN-GROUND CARIBOU - Lent, Peter C. (Canadian Journal of Zoology, 1965)
A study of antler shedding among female barren-ground caribou in northwest Alaska revealed that, in 1961, most, but not all, barren cows shed their antlers before the start of the calving season. In contrast, almost all pregnant cows possessed antlers at the start of the calving season and retained their antlers for up to 1 week post partum. Determination of the proportion of cows with antlers at the start of the calving period provides a means of estimating the calf crop but tends to underestimate the actual natality.It is suggested that the retention of antlers by pregnant cows may be explained by the high level of estrogen production in these individuals, and that the shedding of antlers following parturition may be triggered by a rapid decrease in the output of estrogens. Similar interactions between anterior pituitary and gonadal sex hormones could account for the timing of antler shedding in both male and female caribou.